Experimental and numerical evaluation of heat and mass transfer of a compressed raw earth block wall - Sara Chehade; Nicolas Dujardin; David Giovannacci; Abderrahim Boudenne (Case Studies in Construction Materials)
This study experimentally and numerically analyzes the hygrothermal performance of a wall constructed from compressed raw earth blocks under different thermal and hygric conditions. The goal is to evaluate the ability of unfired, unstabilized raw earth to regulate indoor temperature and humidity levels. Initial tests revealed strong thermal and moisture-regulating properties at the material level, justifying further investigation at the wall scale. A bi-climatic setup exposed the wall’s outer surface to fluctuating temperatures and humidity cycles while maintaining the inner surface at 20°C with varying relative humidity (30–50 % RH). Data on temperature and humidity were collected using sensors at different depths, and a numerical model based on Künzel's approach was applied to predict and analyze temperature and humidity variations. The results showed that the raw earth wall effectively dampened temperature fluctuations and regulated humidity, displaying a temperature gradient of 6°C between depths of 2.5 cm and 7.5 cm during temperature cycles. The wall also functioned as a moisture barrier, with internal moisture levels not stabilizing after 20 days at 80 % relative humidity. The numerical model accurately predicted temperature variations. Designed specifically for internal partitions, this type of wall shows great potential to improve indoor environmental quality by passively regulating temperature and humidity.